Diversity of Salmonella in biofilms and water in a headwater ecosystem. Issue 3 (6th November 2012) - Sha, Qiong; Forstner, Michael R.J.; Hahn, Dittmar
Abstract The diversity of Salmonella was analysed in biofilm and water samples from the spring and slough arms of Spring Lake, the headwaters of the San Marcos River, Texas, during the drought of 2011, with only one potential run‐off event at the beginning of the study. Salmonellae were detected in semiselective enrichment cultures by end‐point PCR during the entire sampling period of (11 sampling events during 2 months). From the spring arm site, 73% of the biofilms and 41% of the water samples were positive for salmonellae, while only 9% of the biofilms and 23% of the water samples were positive from the slough arm site. Salmonellae could be isolated from all positive samples, with higher diversity in biofilms compared with water samples and more strains obtained from the spring arm than from the slough arm. Differences between sites were generally caused by less frequently detected isolates, while the majority of isolates that were present in both biofilms and water from both sites was represented by three strains only. Quantification attempts by quantitative PCR directly in samples without prior enrichment did not result in a reliable detection of salmonellae, suggesting that numbers in all samples were below the detection limit.